Park na torach. Przykład adaptacji wiaduktu kolejowego na teren zieleni = Re-using old railway viaduct as a city park - Łotysz, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An old railway viaduct running along the west banks of Manhattan, had been remaining idle for thirty years. Now it has been turned into a public park. Carefully designed by a renowned architectural company almost instantly became a point of interest for New Yorkers and tourists. This excellent example of modernization of postindustrial relic attracted much attention from promoters of reusing post-industrial heritage.
Keywords: rewitalizacja; park; architektura krajobrazu; dziedzictwo przemysłowe; revitalization; landscape architecture; city park; industrial heritage